Mutual intelligibility between West and South Slavic languages. - Golubović, Jelena; Gooskens, Charlotte (Russian Linguistics, 2015)
In the present study we tested the level of mutual intelligibility between three West Slavic (Czech, Slovak and Polish) and three South Slavic languages (Croatian, Slovene and Bulgarian). Three different methods were used: a word translation task, a cloze test and a picture task. The results show that in most cases, a division between West and South Slavic languages does exist and that West Slavic languages are more intelligible among speakers of West Slavic languages than among those of South Slavic languages. We found an asymmetry in Croatian-Slovene intelligibility, whereby Slovene speakers can understand written and spoken Croatian better than vice versa. Finally, we compared the three methods and found that the word translation task and the cloze test give very similar results, while the results of the picture task are somewhat unreliable.